MEF2C Expression Is Regulated by the Post-transcriptional Activation of the METTL3-m6A-YTHDF1 Axis in Myoblast Differentiation - Yang, Xinran; Ning, Yue; Abbas Raza, Sayed Haidar; Mei, Chugang; Zan, Linsen (Frontiers in Veterinary Science, 2022)
N6-methyladenosine (m6A) plays an essential role in regulating gene expression. However, the effect of m6A on skeletal myoblast differentiation and the underlying mechanisms are still unclear. Here, we ascertained mRNA m6A methylation exhibited declined changes during bovine skeletal myoblast differentiation, and both MEF2C mRNA expression and m6A levels were significantly increased during myoblast differentiation. We found that MEF2C with mutated m6A sites significantly inhibited myoblast differentiation compared with wild-type MEF2C. METTL3 promoted MEF2C protein expression through posttranscriptional modification in an m6A-YTHDF1-dependent manner. Moreover, MEF2C promoted the expression of METTL3 by binding to its promoter. These results revealed that there is a positive feedback loop between these molecules in myoblast differentiation. Our study provided new insights into skeletal muscle differentiation and fusion, which may provide an RNA methylation-based approach for molecular genetics and breeding in livestock as well as for the treatment of muscle-related diseases.